Numerical-Experimental characterization of honeycomb sandwich panel and numerical modal analysis of implemented delamination - AYA BENDADA; Djilali Boutchicha; Adel Chouiter; Mokhtaria Miri (Fracture and Structural Integrity)
The objective of this paper is to investigate the influence of the delamination on the vibration behavior of honeycomb sandwich panel, firstly, numerical characterization to provide the constant properties of the core only are performed using initial finite element model of Representative Volume Element (RVE) which does not take into account the double thickness wall existing in aluminum core structure. According to these initial parameters, finite element model of sandwich composite plate is constructed to extract its elasto-dynamic parameters. In order to validate the numerical results, Experimental Modal Analysis of sandwich plate specimens was performed. Secondly, the double thickness wall is selected to be introduced in the RVE because of important error between numerical and experimental achievements. Comparative study validates the improved mechanical characteristics.